The good, the bad and the ugly: learning from experience to achieve sustainable fisheries - Parma, Ana María (2006)
A broad range of fisheries-management approaches has been used around the world with varying degrees of success. The Fifth International Mote Symposium focused on contrasting strategies and contexts associated with successful experiences with others associated with management failures. A number of general principles for successful fisheries management emerged. These principles emphasize the need to address the causes of management failures directly by creating institutional structures that provide incentives to stop the race for fish and to increase responsibility and accountability of all stakeholders—fishers, scientists, and managers.